Facial artery musculomucosal flaps in oropharyngeal reconstruction following salvage transoral robotic surgery: a review of outcomes. Issue 10 (2nd September 2019) - Asairinachan, A; O'Duffy, F; Li, M P; Fua, T; Chauhan, A; Magarey, M J R; Dixon, B J
Abstract: Objective: There has been little reported on the transoral reconstructive options following salvage transoral robotic surgery. This paper describes the facial artery musculomucosal flap as a method to introduce vascularised tissue to a previously irradiated resection bed. Methods: A facial artery musculomucosal flap was used to reconstruct the lateral pharyngeal wall in 13 patients undergoing salvage transoral robotic surgery for oropharyngeal squamous cell carcinoma. Outcomes recorded include flap and donor site complications, length of stay, and swallowing and speech outcomes. Results: There were no immediate or late flap complications, or cases of delayed wound healing in this series. There were two facial artery musculomucosal related complications requiring surgical management: one bleed from the facial artery musculomucosal donor site and one minor surgical revision. Healing of the flap onto the resection bed was successful in all cases. Conclusion: The facial artery musculomucosal flap provides a suitable transoral local flap option for selected patients undergoing salvage transoral robotic surgery for oropharyngeal malignancies.